Pesticide Exposure and the Incidence of Type 2 Diabetes Mellitus Among Farmers: A Literature Review - Dyah Pramesti Puspawardaya; Suhartono Suhartono; Onny Setiani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from insulin resistance or inadequate insulin secretion. While lifestyle factors are established contributors, prolonged exposure to environmental chemicals is also implicated in its etiology. The intensification of agricultural practices has led to the widespread application of various pesticides, including fungicides, insecticides, and herbicides. Consequently, hazardous compounds from these pesticides can accumulate in the human body, either through direct occupational exposure, as seen in farmers, or indirectly via the consumption of contaminated food and water. Methods: This study employed a PRISMA-guided systematic literature review of peer-reviewed observational studies published between 2015 and 2025. Relevant articles were retrieved from Google Scholar, ScienceDirect, and the Undip E-Journal using predefined keywords related to pesticide exposure, farming populations, type 2 diabetes mellitus, and cholinesterase activity. Studies were included if they assessed occupational pesticide exposure among farmers and reported T2DM-related outcomes, while experimental, animal, review articles, and studies lacking relevant exposure or outcome data were excluded. The PRISMA-based selection process yielded 10 studies for qualitative synthesis. Results: The review identified several occupational factors significantly associated with an increased risk of T2DM. These include a long working period (over 10 years), inadequate use of Personal Protective Equipment (PPE), gender, and the application of more than one type of pesticide. The underlying mechanism involves certain pesticide compounds, particularly Persistent Organic Pollutants (POPs) like organochlorines (e.g., DDE) and organophosphates, which act as endocrine disruptors. Exposure to these chemicals is linked to reduced cholinesterase enzyme levels and pancreatic beta-cell dysfunction, leading to insulin resistance and glucose intolerance. Conclusions: There is a significant relationship between pesticide exposure and the incidence of T2DM among farmers. Key risk factors are prolonged exposure, unsafe work practices, and the use of specific pesticide types. Mitigation efforts, such as strict enforcement of PPE usage and farmer education on the risks of pesticide handling, are crucial as preventive measures to reduce the burden of T2DM in this vulnerable group.